Pengaruh Kepemimpinan Transformasional Terhadap Komitmen Organisasional Dan Organizational Citizenship Behavior Yang Di Mediasi Oleh Kepuasan Kerja - Elatotagam, Joni (JURNAL RISET BISNIS DAN MANAJEMEN, 2017)
The purpose of this study is to examine and analyze the Influence of Transformational Leadership on Organizational Commitment and Organizational Citizenship Behavior Mediated by Job Satisfaction, to employees at the Office of the Regional Development Planning Board of Puncak Regency. The population in this study is all employees in the Office of the Regional Development Planning Board Puncak, which amounted to 33 employees and samples taken from the entire population. This research uses quantitative approach. Analytical technique using Line Analysis Technique using SPSS 22Keywords: Transformational Leadership, Organizational Commitment, Organizational Citizenship Behavior, Job Satisfaction